Nipah Virus–Another Threat From the World of Zoonotic Viruses - Skowron, Krzysztof; Bauza-Kaszewska, Justyna; Grudlewska-Buda, Katarzyna; Wiktorczyk-Kapischke, Natalia; Zacharski, Maciej; Bernaciak, Zuzanna; Gospodarek-Komkowska, Eugenia (Frontiers in Microbiology, 2022)
Among the diseases that pose a serious threat to public health, those caused by viruses are of great importance. The Nipah virus (NiV) virus belonging to the Paramyxoviridae family. NiV was reported in Malaysia in 1998/1999. Due to its high mortality in humans, its zoonotic nature, the possibility of human-to-human transmission, and the lack of an available vaccine, the World Health Organization (WHO) has recognized it as a global health problem. Depending on strain specificity, neurological symptoms and severe respiratory disorders are observed in NiV infection. In most confirmed cases of NiV epidemics, the appearance of the virus in humans was associated with the presence of various animal species, but generally, bats of Pteropus species are considered the most important natural animal NiV reservoir and vector. Consumption of contaminated food, contact with animals, and ‘human-to-human', close direct contact, were identified as NiV transmission routes. Due to the lack of vaccines and drugs with proven effectiveness against NiV, treatment of patients is limited to supportive and prophylactic.